Study of non-alcoholic fatty liver disease in metabolic syndrome - Shaikh, Mohammed Aslam; P., Bhanuprakash (International Journal of Advances in Medicine, 2018)
Background: Metabolic syndrome is a clustering of risk factors that increase an individual’s probability of developing atherosclerotic cardiovascular disease, type 2 diabetes mellitus and all cause mortality. Since primary NAFLD has strong association with metabolic syndrome as a whole and various components of metabolic syndrome, it is being debated whether NAFLD is a hepatic component of metabolic syndrome. Hence this study was done to study the prevalence of non-alcoholic fatty liver disease in healthy individuals and in patients with metabolic syndrome and to establish a relationship between NAFLD and Metabolic syndrome. Methods: A total of 122 patients - 61 with metabolic syndrome and 61 without metabolic syndrome fulfilling inclusion and exclusion criteria who presented to the Medicine outpatient Department of Ramaiah Medical College, Bangalore, between October 2014 and September 2016 were included in the study. Baseline variables, laboratory parameters, ultrasound abdomen findings were compared between the groups. Results: Mean age of the subjects in metabolic syndrome group and non-metabolic syndrome group were 52.4±15.4 and 50.7±15.4years respectively. Mean triceps skin fold thickness (in cms) for the subjects in metabolic syndrome group and non-metabolic syndrome group were 19.16±6.1 and 7.59±2.57 respectively (P <0.05). Prevalence of fatty liver on ultrasonography in metabolic syndrome and non-metabolic syndrome were 42.62 % and 21.31% respectively. Overall prevalence of NAFLD was 31.97 %. Conclusions: Overall prevalence of NAFLD from current study was 31.97%. The prevalence of NAFLD was significantly higher in persons with metabolic syndrome than persons without metabolic syndrome.